Peningkatan Kemampuan Berbahasa Anak Usia 5-6 Tahun Melalui Media Spin Board di RA Rahmah El-Yunusiyyah Padang Panjang - Nursalehah Nursalehah; Juliwis Kardi; Sri Intan Wahyuni (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The problem behind this research is that the language skills of children aged 5-6 years in Class B of the tulip group at RA Rahmah El-Yunusiyyah Padang Panjang have not developed, such as children who have not been able to compose simple sentences in a complete structure, children have not been able to understand the rules in a game. Based on this, researchers try to apply spin board media in the hope that it can improve children's language skills well. This study aims to improve the language skills of children aged 5-6 years through spin board media. Spin board as an interactive learning media, designed to facilitate the development of children's language skills through fun and educational games. The study used a classroom action research method with a sample of 12 children in class B of the Tulip group of RA Rahmah El-yunusiyyah Padang Panjang. Data was collected through observation, documentation and research. The results of this study indicate that the improvement of children's language skills through spin board media has increased. This can be seen from before taking action, where from pre-research the number of scores achieved by children is only 26%. Then the researchers took action for 2 cycles, where in each cycle there were 3 meetings. The first meeting in cycle I the score obtained by the child through the spin board media was 27%, then at the second meeting of cycle I increased to 30% and at the third meeting in cycle I the score achieved by the child through the spin board media was 48%. This shows that every meeting the scores achieved by children always increase, but have not met the ideal score standard of 72%. Therefore, researchers continued to cycle II. The score at the first meeting in cycle II was 50% then experienced an increase in the second meeting of 55% and continued the third meeting of cycle II experienced an increase in children's learning process using spin board media of 80%. From each cycle carried out, it can be concluded that this research was successful.